Juridical Review the Role of the Notary Honor Council in Providing Sanctions against Notary That Violates the Code of Ethics of Notary Position - Damayanti, Fera (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This research will be examined in this study are: What is the mechanism for imposing sanctions on notaries who violate the notary's code of ethics and the efforts that can be made by a notary who is imposed with a sanction for violating the notary's code of ethics to file an objection. The approach method used is a normative juridical approach and the specifications used in this study are analytical descriptive research. Based on the results of the study it can be concluded that for Notaries who violate the code of ethics, the Ethics Council can impose sanctions on the violators, sanctions imposed on members of the Indonesian Notary Association who violate the code of ethics can be in the form of: Reprimand, Warning, Temporary Dismissal from Association Membership, Dismissal With Respect from Association Members, and Disrespectful Dismissal from Association Members. However, the dismissal sanction given to a Notary who violates the code of ethics is not in the form of dismissal from the notary position but dismissal from membership of the Indonesian Notary Association. So that the sanction seems to have less binding power for Notaries who violate the code of ethics. Notaries who have been sanctioned for violating the code of ethics can defend themselves and can appeal in stages against the decisions of the Regional Ethics Council to the Regional Ethics Council and the Central Ethics Council as a final level examination.Keywords: Notary, Code of Ethics, Sanctions